Mesin ayak dua saluran dilengkapi pengarah untuk beras jagung - Yohanes Benediktus Yokasing; Amiruddin Abdullah; Stanislaus Tamelab (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2022)
Sieve machine is used to separate groups of granules based on size. Most separation sieves on 2 groups of sifted/filtered grains move immediately, but the unfiltered grains are removed by the operator turning the sieve sideways or lifting the unfiltered material. In addition, the sifted material is usually poured directly on the sieve wire. This slows down the sifting process and the buildup can damage the sieve. On the other hand, sieve materials such as corn rice products, require 2 sizes of sieve wire holes. For that, do the design, made and studied the function, "The Sieve Machine’s two channel Equipped with Directions for Rice Corn". The specifications of the sieve machine as follows; has 2 sifting channels, the sieve filter can be replaced, the filter is driven by a swing arm, dynamo drive 3/4 hp, rotation 1400 rpm, the capacity for one stage is ± 44.8 kg/hour, the capacity for corn rice ± 22 kg/hour (it's time to change the sieve). The study of engine performance on several variables resulted in the smaller the angle of lightening the capacity increases, it is inversely proportional to the length of the spring and rotation. At angle 50 sieve capacity is 23.3 kg/hour, with length of the spring is 90.5 mm, and on length of spring becomes 100.5 mm, sieva capacity of 24.6 kg/hour. For angle 150, the capacity is reduced by 20.4 kg/hour. At rotation 230 rpm, 50 angle, decreased capacity, only 20.3 kg/hour, spring length 90.5 mm.